1991
DOI: 10.1172/jci115063
|View full text |Cite
|
Sign up to set email alerts
|

Mucin production by human colonic carcinoma cells correlates with their metastatic potential in animal models of colon cancer metastasis.

Abstract: Patients with mucinous colorectal cancers characteristically present with advanced disease, however, the relationship between mucin production by colon cancer cells and their metastatic potential remains unclear. We therefore sought to define the relationship between mucin production by human colon cancer cells and metastatic ability by employing animal models of colon cancer metastasis. LS LiM 6, a colon carcinoma cell line with high liver metastasizing ability during cecal growth in nude mice produced twofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 28 publications
6
113
0
1
Order By: Relevance
“…It is not yet clear why patients with STn-positive tumours should have a worse prognosis than those with STn-negative tumours. Sialomucins have been shown in colon cancer model systems to be important in metastasis (Bresalier et al, 1991), and most metastases of gastric cancer express STn (David et al, 1992). In addition, mucins bearing STn antigen can mediate inhibition of natural killer cell cytotoxicity, thereby providing a mechanism for immune escape (Ogata et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear why patients with STn-positive tumours should have a worse prognosis than those with STn-negative tumours. Sialomucins have been shown in colon cancer model systems to be important in metastasis (Bresalier et al, 1991), and most metastases of gastric cancer express STn (David et al, 1992). In addition, mucins bearing STn antigen can mediate inhibition of natural killer cell cytotoxicity, thereby providing a mechanism for immune escape (Ogata et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in athymic nude mice has reported that GalNAc␣-O-bn could significantly reduce liver colonization by the mucin-secreting variant LiM6 of colon carcinoma LS174T cells, which mainly expresses the mucin MUC2. 48 However, our previous work has shown that this GalNAc-␣-O-bn induced particular effects in the model of mucin-secreting HT-29 cells, specifically, i.e., an inhibition in the secretion of MUC5AC in the apical culture medium, and the disappearance of MUC1 at the apical membrane, these glycoproteins remaining accumulated inside the cells. 49 -51 In contrast, the basolateral glycoprotein E-cadherin was not affected (data not shown).…”
Section: Immunofluorescence Analysis Of the Distribution Of E-cadherimentioning
confidence: 92%
“…The mucin family of anti-adhesion molecules have been implicated in the biological behaviour and progression of several types of cancer (Bresalier et al, 1991;Gendler and Spicer, 1995). The mucin MUC-1, which is expressed at the apical cell surface of many normal secretory epithelial cells (Ho et al, 1993), contains an extra-cellular domain that extends above most other cell membrane-associated proteins (Hilkens et al, 1992;Hilkens et al, 1995).…”
mentioning
confidence: 99%